Leaf-cutting ants revisited: Towards rational management and control - Montoya Lerma, James (2012)
Leaf-cutting ants, being the principal herbivores and ecosystem engineers in the Neotropics, have been considered to be a keystone species in natural ecosystems and agroecosystems, due to the direct and indirect eﬀects of their plant defoliation activities. This review summarizes current concepts of the biological and ecological importance of leaf- cutting ants. The ants? pest status is brieﬂy assessed from both ecological and evolutionary points of view. A general overview of control measures is provided. Leaf-cutting ants have evolved physical, symbiotic and behavioural mechanisms that allow them to overcome the chemical, biological, mechanical and cultural methods that have been used to manage their populations. Given the highly complex ecology of these ants, simple methods of control should not be expected. Sound management strategies must alternate between, and combine, diﬀerent methods.